Treatment of Levodopa-induced dyskinesia with Vitamin D: A Randomized, double-blind, placebo-controlled trial - Amir Hassan Habibi; Arezo Anamoradi; Gholam Ali Shahidi; Saeed Razmeh; Elham Alizadeh; Karim Moradian Kokhedan (MDPI AG, 2018)
Dyskinesia refers to any involuntary movement, such as chorea, dystonia, ballism that affect any part of the body. Levodopa-induced dyskinesia is a neurological disorder that afflicts many patients with Parkinson disease usually 5 years after the onset of levodopa therapy and can cause severe disability. The pathophysiology of this dyskinesia is complex and not fully understood. However, the association between vitamin D and Parkinson disease is interesting. The present study was conducted to evaluate the effect of vitamin D on levodopa induced dyskinesia in patients with Parkinson's disease .In this Double blind clinical trial, 120 patients with PD divided into two groups randomly, vitamin D and placebo group. A dose of 1000 IU/d was selected, Demographic information is registered. In the first visit, three variables have been measured which were the duration, severity of dyskinesia and unified Parkinson's disease rating scale (UPDRS). These variables were measured again after 3 months and the data was analyzed using SPSS 22. There are no differences between two groups after 3 months. This study revealed, vitamin D has no effects on improvement of levodopa induced dyskinesia.